Degree of satisfaction following full-endoscopic cervical foraminotomy - Tonosu, Juichi (J Spine Surg, 2020)
BACKGROUND: Foraminotomy has been reported to be effective for the treatment of cervical radiculopathy (CR). Foraminotomy has been performed by an open approach or minimally invasive approach using a microscope or endoscope. A review of the literature has revealed that both the open and minimally invasive approach provide good clinical results. Since the introduction of full-endoscopic cervical foraminotomy (FECF) followed by microendoscopic cervical foraminotomy, we adopted FECF in 2016. The purpose of this study was to evaluate the degree of satisfaction following FECF for CR. METHODS: A total of 109 consecutive patients underwent FECF for CR. All operations were performed at Iwai Orthopaedic Medical Hospital. Patient background information and operative data were collected. The numerical rating scale (NRS) score for the arm was assessed preoperatively and postoperatively at the time of discharge from the hospital. The satisfaction score was also recorded at discharge and the 3 months after the operation. RESULTS: In total 109 patients, the mean age was 51.3 years; 22.9% were female and 77.1% were male. The cervical level most frequently operated on was C6/7, followed by C5/6. The mean hospital stay was 4.7 days. The mean operation time was 61.7 minutes. The estimated blood loss was 0 to 10 mg in all cases. One patient exhibited temporary postoperative muscle weakness, although he recovered within 1 year. There was one case of dural tear, and no cases of nerve root injury or surgical site infection. There was one case of reoperation by microendoscopic surgery in 3 months due to insufficient improvement. Preoperative NRS scores for the arm was 4.6 and it improved significantly postoperatively to 2.1 for the entire study group. The mean satisfaction score at discharge was 7.5. The mean score at 3 months after the operations was 7.4. CONCLUSIONS: Degree of satisfaction following FECF for CR was high 3 months after the operation.